Adults with Loeys–Dietz syndrome and vascular Ehlers–Danlos syndrome: A cross‐sectional study of health burden perspectives. Issue 1 (6th November 2019) - Johansen, Heidi; Velvin, Gry; Lidal, Ingeborg
Abstract: The aim is to study adults with vascular Ehlers–Danlos syndrome (vEDS) and Loeys–Dietz syndrome (LDS) with regard to sociodemographic characteristics, perceived vascular‐ and multi‐organ symptom burdens, and health services utilization. This is a cross‐sectional study. In 2018, a postal questionnaire was sent to 71 individuals with genetically verified LDS types 1–4 or vEDS, age ≥ 18 years, recruited through a National Resource Centre for Rare Disorders in Norway. Eighteen patients with vEDS and 34 patients with LDS subtypes 1‐4 participated, the response rate was 74%. Median age was 43.5 (range 18‐68) years, and 58% were women. Median age at diagnosis was 34 years (range: 6–63). Severe vascular‐ and multi‐organ symptom burdens were found, and chronic pain was reported by 79%. Most respondents (87%) had cardiovascular surveillance visits, 58% yearly or more often, and still 29% had no antihypertensive medications. Three quarters communicated diagnosis‐related concerns with their general practitioner. A considerable group (31%) had left work before retirement age. Healthcare professionals should be aware of the spectrum of health burden in adults with vEDS and LDS. A verification of the diagnosis is crucial to counseling, including medical follow‐up, education, and work, and advices on precaution and life style decisions.